2011
DOI: 10.1179/1465328111y.0000000031
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy and its correlates among HIV-infected children at an HIV clinic in New Delhi

Abstract: It is possible to achieve high adherence to ART in a resource-limited setting. Caregiver recall is a reliable and inexpensive tool for measuring adherence. Paediatric adherence to ART is influenced by numerous factors and larger studies are needed to address the issue in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 27 publications
5
25
1
8
Order By: Relevance
“…The use of treatment reminders was associated with better adherence while the use of PI-based regimens predicted poorer adherence. The adherence rate in the current study is better than those reported from several low, middle and high income countries (Bhattacharya & Dubey, 2011;Kim, Gerver, Fidler, & Ward, 2014;Nyogea et al, 2015;Reda & Biadgilign, 2012;Ugwu & Eneh, 2013). …”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The use of treatment reminders was associated with better adherence while the use of PI-based regimens predicted poorer adherence. The adherence rate in the current study is better than those reported from several low, middle and high income countries (Bhattacharya & Dubey, 2011;Kim, Gerver, Fidler, & Ward, 2014;Nyogea et al, 2015;Reda & Biadgilign, 2012;Ugwu & Eneh, 2013). …”
Section: Discussioncontrasting
confidence: 52%
“…Its continued positive clinical impact depends on taking more than 95% of prescribed doses (Jobanputra et al, 2015;WHO, 2013;Zoufaly et al, 2013;Bhattacharya & Dubey, 2011;MOH, 2007). Several factors affect the rate of treatment adherence among children including drug regimen, caregivers, and society and culture related factors (Castro, Gonzalez, & Perez, 2015;Haberer & Mellins, 2009) (Hagstromer, Lundstedt, Balcha, & Bjorkman, 2013;Muller et al, 2011), (Reda & Biadgilign, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente, el VIH se considera una enfermedad crónica (Bhattacharya & Dubey, 2011). La enfermedad crónica durante la infancia tiene un gran efecto psicológico, social y familiar.…”
Section: Introductionunclassified
“…A pesar de los grandes avances en la terapia antirretroviral, su ingesta no garantiza el control de la enfermedad en los niños (Dobrova-Krol et al, 2010); para que pueda ser efectiva, se requiere una elevada AT de por lo menos el 95% (Bhattacharya & Dubey, 2011). El concepto de "adhesión terapéutica" se define como 'una implicación activa y voluntaria del paciente en un comportamiento aceptado de mutuo acuerdo con el médico, cuyo fin es producir un resultado terapéutico deseado' (Bhattacharya & Dubey, 2011;Villa & Vinaccia, 2006).…”
Section: Introductionunclassified
See 1 more Smart Citation